GAMBARAN LINGKUNGAN FISIK RUMAH TERHADAP KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT PADA BALITA DI PUSKESMASKAWANGU - YUBLINA JAMI HAHA; ADRIANA NARA; MARIA KARERI HARA; JOHANA BABANG ATAMEHA (JURNAL KESEHATAN PRIMER, 2017)
Introduction: Acute Respiratory Infection (ARI) is a disease caused by infectious agents that are transmitted from human to human. ARI is influenced by the lack of family knowledge of the importance of environmental hygiene to health. Based on data from the District Health Office of East Sumba in 2015, people with ISPA ranks first of 10 disease patterns is 21.227 cases. The purpose of this study is to know the description of the physical environment of the house against the incidence of acute respiratory infections in infants at PuskesmasKawangu Pandawai District, East Sumba Regency. Method: This type of research used descriptive method. Sampling technique Accidental Sampling and research instrument using questionnaire. Result: From 95 respondents who have physical house environment fulfill good criteria that is 63,2%, but there are still some respondent who have physical environment of house with criterion less that is 9,4%. Conclusion: this is due to the lack of family knowledge about the requirements of the physical environment of the house is good, the family behavior to realize or know how to maintain health or prevent things that harm health and still strong community culture related to the way home making where almost all respondents have stage houses made of boards.